2019
DOI: 10.1002/pts.2432
|View full text |Cite
|
Sign up to set email alerts
|

Role of package headspace on multilayer films subjected to high hydrostatic pressure

Abstract: The objective of this study was to systematically examine the effect of high‐pressure processing and package headspace on package integrity and properties. Working pressures were 400 and 600 MPa, and starting vessel temperatures were 30°C, 60°C, and 90°C. Coextruded and laminated multilayers packaging films were studied: film A: (PA/EVOH/PP) and film B: (PET‐AlOx‐OC/PA6/PP), respectively. The films were made into pouches (0.05 m × 0.10 m) and filled with 30‐mL water as a model food. Various headspace volumes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(84 reference statements)
1
7
1
Order By: Relevance
“…Packaging seals remained intact in all treated films and there was no leakage or hole in the pouches. The obtained results differ from the earlier reports on HP treatment on laminated films (e.g., bilayer metPET, PET/LLDPE, PA/EVOH/PP) (Al‐Ghamdi et al., 2019; Sansone et al., 2014). It was reported that films processed under HP or a combination of HP and high temperature resulted in visual defects (white spots) and delamination of the outer film.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Packaging seals remained intact in all treated films and there was no leakage or hole in the pouches. The obtained results differ from the earlier reports on HP treatment on laminated films (e.g., bilayer metPET, PET/LLDPE, PA/EVOH/PP) (Al‐Ghamdi et al., 2019; Sansone et al., 2014). It was reported that films processed under HP or a combination of HP and high temperature resulted in visual defects (white spots) and delamination of the outer film.…”
Section: Resultscontrasting
confidence: 99%
“…Al‐Ghamdi et al. (2019) made a similar observation for PA/EVOH/PP and PET‐AlOx‐OC/PA6/PP films, where the overall thicknesses of the films were not affected after the HP processing. Pouches sustained the largest exerted pressure of 600 MPa for 15 min, and no deformation or any form of visual defects were detected in pouches (e.g., blisters, opacification, and delamination).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…For the PET printing /PET met /LDPE coex laminate, the increases in WVTR and OTR are justified by the microscopic damage presented on the surface of the material, as reported in a previous study (Marangoni Júnior, de Oliveira, Dantas, et al, 2020). In addition, other studies in the literature, where metallized structures or other coatings, processed by different high‐pressure conditions were also evaluated, resulting in discontinuation of metallization after high‐pressure processing (Al‐Ghamdi, Sablani, Rasco, & Cánovas, 2019; Ayvaz et al., 2012; Bull et al., 2010; Caner, Hernandez, & Pascal, 2000; Galotto, Ulloa, Guarda, Gavara, & Miltz, 2009; Galotto et al., 2010), which was not possible to evaluate the material studied due to the presence of printing on the outer layer of PET.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic analysis of a multilayer film surface can be done using scanning electron microscopy (SEM) to help in the detection of swelling, delamination, surface cracks, and holes after processing (Marangoni Júnior, Cristianini, Padula, & Anjos, 2019). The changes occurring in the crystal structure and crystal size of the polymers when undergone processing can be visualized in X‐ray diffraction (Al‐Ghamdi, Rasco, Tang, Barbosa‐Cánovas, & Sablani, 2019). Positron annihilation lifetime spectroscopy (PALS) is an informative technique that can be used for characterization of valance defects in crystals and voids volumes in polymers (Tang, Selim, Dhawan, Varney, & Barbosa‐c, 2014).…”
Section: Properties Of Multilayer Filmsmentioning
confidence: 99%